Synthesis and Characterization of Semisynthetic Metallothermolysin - Khalid, Syarajatul Erma (2008)
Modification of native enzyme has gone through various strategies and evolution of the process itself. Thermolysin (TLN) from Bacillus thermoproteolyticus rokko was modified as a semisynthetic metallothermolysin which comprises enzyme, ligand and metal ion. Ligands used were benzamidine (BEN), 1,10-phenanthroline (PHN), p-aminobenzamidine (PBZ) and ethanolamine (ETA). The metal ions chosen were magnesium (Mg2+), zinc (Zn2+), calcium (Ca2+) and nickel (Ni2+). The semisynthetic metallothermolysin activities were evaluated on hydrolysis reaction of azocasein. Among the four ligands, complex of TLN-PBZ showed the highest specific activity (2219.5 Unit per mg (U/mg)) at optimum PBZ concentration of 0.6 mM. The study followed by the attachment of Mg2+ to TLN-PBZ complex which gave the best specific activity compared to other metal ions (39406.4 U/mg). The optimum concentration of Mg2+ was found best at 0.08 mM. Several parameters were also investigated such as studies on effect of pH, temperature, time course and thermostability. As a result, the semisynthetic metallothermolysin maintained at pH surrounding of 7.0 in tris-HCl buffer and found optimum at 80oC for reaction up to 3 hours (96.7% of relative activity). For thermostability test, the semisynthetic metallothermolysin can retain its activity up to 90% at pre-heated temperature of 80oC. Electronic absorption like the UV/Visible (UV/Vis) and UV/Fluorescence spectrophotometer and Circular Dichroism (CD) spectropolarimetry method were used to characterize the optical properties of metallothermolysin. In UV/Vis spectrophotometer, the binding of PBZ to TLN curve caused a bathocromic shift (λmax from 279 nm to 274 nm) and became hypsochromicsm (λmax from 274 nm to 272 nm) with the additional of Mg2+. Changes in UV/Vis were also supported by UV/Fluorescence, when changes happened to the emission characteristic of TLN-PBZ spectrum (373.2 nm) and the spectrum continues to shift (374.0 nm) for TLN-PBZ-Mg. The CD spectropolarimetry suggested some changes of α helix and β sheet at far UV molar ellipticity readings with decreased of α helix from 37% (TLN) to 20.6% (TLN-PBZ) and then to 19.8% (TLN-PBZ-Mg). Meanwhile, a further decrease of β sheet from 32.6% (TLN) to 18.7% (TLN-PBZ) and then to 11.0% (TLN-PBZ-Mg) was also observed.